Associations between hypovitaminosis D, adiposity indices and insulin resistance in adolescents: mediation analyses from NHANES 2011–2018 - Yaping Deng; Yingting Luo; Yilei Shen; Yong Zhao; Wei Cao; Jie Cao; Lijuan Xu; Lin Kong (Nutrition & Diabetes)
Abstract Background As all kown, both hypovitaminosis D and insulin resistance (IR) have been linked to adiposity. However, the extent of adiposity’s mediating influence on the hypovitaminosis D-IR relationship among adolescents remains to be elucidated. Additionally, the intricate effects of obesity and blood lipid profiles on IR are not yet fully understood. Methods We conducted a comprehensive analysis of NHANES data from 2011 to 2018, examining the correlation between adiposity indices such as Body Mass Index (BMI), Fat Mass Index (FMI, defined as the ratio of fat mass to height squared), hypovitaminosis D, and IR. We employed the XGBoost algorithm to identify key factors significantly influencing IR, thereby deepening our insight into the link between adiposity and insulin resistance. Furthermore, we applied mediation analysis to precisely assess the mediating role of adiposity indices in the relationship between hypovitaminosis D and IR. Results Our study revealing significant correlations between adiposity indices, hypovitaminosis D, and IR after variable adjustment. Notably, subgroup analysis indicated a pronounced hypovitaminosis D -adiposity association in female adolescents, which was not observed in males. The XGBoost algorithm pinpointed obesity and blood lipid indicators significantly affecting IR, with total fat mass, triglyceride, cholesterol, BMI, and FMI ranked by descending importance. Mediation analysis disclosed that adiposity indices mediate a substantial portion of the hypovitaminosis D -IR relationship, with FMI (43.84%, p < 0.001) and BMI (40.87%, p < 0.001) showing significant mediating effects. Conclusion The study confirmed significant correlations between adiposity indices, hypovitaminosis D, and IR in adolescents, with gender-specific differences in the hypovitaminosis D -adiposity link. Cholesterol was found to have a more substantial influence on IR than BMI and FMI. Furthermore, FMI was identified as a more potent mediator of the hypovitaminosis D-IR relationship compared to BMI, highlighting its importance in the pathophysiology of insulin resistance in adolescents.